'I don't want to go back into the closet just because I need care': recognition of older LGBTQ adults in relation to future care needs. Issue 2 (3rd March 2020) - Löf, Jenny; Olaison, Anna
ABSTRACT: There is increasing awareness in research about the social service needs of older LGBTQ adults. However, there are few studies that deal with differences in this community regarding elder care services. As a rule, transgender individuals are not included in these studies. This study focuses on how older Swedish LGBTQ adults reason about openness in an elder care context concerning their future needs for services and adopts Nancy Fraser's theoretical framework of recognition. The material consists of fifteen semi-structured interviews with older LGBTQ adults. The results indicate that the main concern for older LGBTQ individuals is being accepted for their preferred sexual orientation and/or gender identity in elder care. However, there were differences regarding that concern in this LGBTQ group. There were also a variety of approaches in the group as to preferences for equal versus special treatment with respect to their LGBTQ identity. In addition, there were differences as to whether they prefer to live in LGBTQ housing or not. The findings contribute to existing knowledge by highlighting the diverse views on elder care services in both this group of interviewees and its subgroups. These findings emphasise the importance of the social work practice recognising different preferences and having an accepting approach. The results can further provide guidance on how to design elder care services for older LGBTQ adults.